Factors Associated with Women’s Decision to Become Commercial Sex Workers in Banjarsari, Surakarta, Central Java - Syefira Ayudia Johar; Argyo Demartoto; C.S.P Wekadigunawan (Masters Program in Public Health, 2018)
Background: In Indonesia, the number of new HIV cases in 2016 was 41.250, and AIDS cases was 7,491. HIV infection predominantly (67.6%) occur heterosexually. In Central Java, the number of Di Indonesia, new HIV cases in 2016 was 4.032, and AIDS cases was 1.402. Surakarta City has the second highest cases of HIV in Central Java after Semarang District with 38 HIV cases and 46 AIDS cases in September 2017. This study aimed to analyze factors associated with women’s decision to become commercial sex workers in Banjarsari.Subjects and Method: This was an analytical observational study with case control design. The study was conducted in Banjarsari, Surakarta, Central Java. A total sample of 200 study subjects consisting of 100 female commercial sex workers and 100 non sex workers. The dependent variable was women’s decision to become commercial sex worker. The independent variables were knowledge of sexually-transmitted disease, family income, pro-commercial sex worker family support, snobbish life style, and access to whore house. The data were collected by questionnaire and analyzed by multiple logistic regression.Results: Women’s decision to become commercial sex worker was negatively associated with good knowledge of sexually-transmitted disease (OR= 0.03; 95% CI= 0.01 to 0.18; p<0.001), high family income (OR= 0.01; 95% CI<0.01 to 0.05; p<0.001). Women’s decision to become commercial sex worker was positively associated with strong pro-commercial sex worker family support (OR=8.15; 95% CI= 2.63 to 25.23; p<0.001), snobbish life style (OR= 6.20; 95% CI= 1.81 to 21.24; p= 0.004), and access to whore house (OR= 8.52; 95% CI=2.49 to 29.17; p= 0.001).Conclusion: Women’s decision to become commercial sex worker has negative association with good knowledge of sexually-transmitted disease, high family income. Women’s decision to become commercial sex worker has positive association with strong pro-commercial sex worker family support, life style, and access to whore house.Keyword: Women’s decision, commercial sex worker, knowledge, family income, family support, life style, access to whore houseCorrespondence: Syefira Ayudia Johar. Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami 36 A, Surakarta 57126, Central Java. Email: syefira48@gmail.com. Mobile: +6282136422448.Journal of Epidemiology and Publich Health (2018), 3(1): 72-82https://doi.org/10.26911/jepublichealth.2018.03.01.06